The experiences of postnatal women and healthcare professionals of a brief weight management intervention embedded within the national child immunisation programme - Natalie Tyldesley-Marshall; Sheila M Greenfield; Helen M Parretti; Kate Jolly; Susan Jebb; Amanda J Daley (BMC, 2021)
Abstract Background After childbirth, most women do not lose the extra weight gained during pregnancy. This is important because postnatal weight retention contributes to the development of obesity in later life. Research shows that postnatal women living with overweight would prefer to weigh less, are interested in implementing weight loss strategies, and would like support. Without evidence for the benefit of weight management interventions during pregnancy, postnatal interventions are increasingly important. Research has focused on intensive weight loss programmes, which cannot be offered to all postnatal women. Instead, we investigated the feasibility of a brief intervention delivered to postnatal women at child immunisation appointments. This qualitative study explored the views of women who received the intervention and healthcare professionals who delivered it. Methods The intervention was delivered within the context of the national child immunisation programme. The intervention group were offered brief support encouraging self-management of weight when attending general practices to have their child immunised at two, three and four months of age. The intervention involved motivation and support from practice nurses to encourage women to make healthier lifestyle choices through self-monitoring of weight and signposting to an online weight management programme. Nurses provided external accountability for weight loss. Women were asked to weigh themselves weekly and record this on a weight record card. Nested within this trial, semi-structured interviews explored the experiences of postnatal women who received the intervention and nurses who delivered it. Results The intervention was generally acceptable to participants and child immunisation appointments considered a suitable intervention setting. Nurses were hesitant to discuss maternal weight, viewing the postnatal period as a vulnerable time. Whilst some caveats to implementation were discussed by nurses, they felt the intervention was easy to deliver and would motivate postnatal women to lose weight. Conclusions Participants were keen to lose weight after childbirth. Overall, they reported that the intervention was acceptable, convenient, and, appreciated support to lose weight after childbirth. Although nurses, expressed concerns about raising the topic of weight in the early postnatal period, they felt the intervention was easy to deliver and would help to motivate women to lose weight.